Pretreatment neutrophil to lymphocyte ratio as prognostic factor in metastatic breast cancer treated with cyclin dependent kinase 4/6 inhibitors - Rottier, Pauline; Emile, George; Johnson, Alison; Levy, Christelle; Allouache, Djelila; Hrab, Ioana; Segura, Carine; Morel, Adeline; Villemin, Maud; Dubot-Poitelon, Coraline; Boismoreau, Louis; Cherifi, François; et al. (Frontiers in Oncology, 2023)
Background Cyclin dependent kinase inhibitors (CdK4/6i) changed the course of hormone receptor positive (HR+) HER2 negative (HER2-) metastatic breast cancer (mBC). To date, no factors have been shown to predict response to CdK4/6i. Neutrophil-to-lymphocyte ratio (NLR), an indicator of the host systemic inflammatory response, is an independent prognostic factor for survival in cancers. We conducted this study to evaluate the impact of NLR on survival in mBC patients treated with first line CdK4/6i. Methods All mBC patients treated with first line CdK4/6i between November 2015 and December 2019 were retrospectively included. The biomarker threshold was defined using ROC curves. We analyzed progression free survival (PFS), overall survival (OS), 12-month PFS and response rate according to NLR in univariable and multivariable analysis. Results A total of 126 patients treated with palbociclib (n=101), ribociclib (n=18) or abemaciclib (n=7) were included, with a median follow-up of 33 months [range: 2.9–57]. Median age was 65 years [29-86], 40% patients had good performance status (ECOG-PS 0). Most patients (71%) were included at the metastatic relapse stage and 29% had only bone metastases. Median PFS and median OS were 27 and 51 months, respectively. High NLR (≥ 2.53) was significantly associated with worse PFS (Hazard Ratio (HR)=0.50, CI95% = [0.32–0.79]) and worse OS (HR=0.45, [CI95%: 0.23–0.87]). In multivariable analysis, NLR and ECOG PS were independently factors associated with PFS (p=0.016 and p=0.001, respectively). Conclusion High NLR was associated with worse PFS and OS in HR+ HER2- mBC patients treated with first line CdK4/6i. NLR is a reliable and inexpensive prognostic marker, easily accessible in routine clinical practice, which could help optimize the therapeutic strategy. These results need to be confirmed in larger prospective studies.